2020
DOI: 10.1007/s42452-020-03529-w
|View full text |Cite
|
Sign up to set email alerts
|

Facile biogenic synthesis of silver nanoparticles (AgNPs) by Citrus grandis (L.) Osbeck fruit extract with excellent antimicrobial potential against plant pathogens

Abstract: Biogenic silver nanoparticles (AgNPs) were synthesized by using Citrus grandis (L.) Osbeck fruit extract through a simple one step method by reducing silver nitrate (AgNO 3) at room temperature. Citrus grandis (L.) Osbeck is an indigenously available edible citrus fruit tree in Northeast India and sub-Himalayan foot hills. Formation of AgNPs were confirmed primarily by UV-Vis spectrophotometer and extensively characterized by TEM and XRD. The plasmon resonance at 435 nm confirmed the formation of AgNPs and TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although this effect was not synergistic, it should be noted that the GO MIC was reduced from 0.14 to 0.04 mg mL −1 in the presence of MnFe 2 O 4 /Ag-NC, and this amount is lower than that obtained by Zabihi et al, who reported an MIC of 0.3 mg mL −1 of GO against E. coli [34]. In terms of the silver concentration, studies have reported that inhibitory doses higher than 10 µg mL −1 of different biogenic AgNPs inhibit P. syringae, either alone or combined with other antibiotics [35][36][37][38]. Thus, by using MnFe 2 O 4 /Ag-NC, we reported a further reduced concentration of silver acting efficiently against P. syringae when combined with essential oils.…”
Section: Antimicrobial Activity Of Mnfe 2 O 4 /Ag-nc Combined With Es...mentioning
confidence: 98%
“…Although this effect was not synergistic, it should be noted that the GO MIC was reduced from 0.14 to 0.04 mg mL −1 in the presence of MnFe 2 O 4 /Ag-NC, and this amount is lower than that obtained by Zabihi et al, who reported an MIC of 0.3 mg mL −1 of GO against E. coli [34]. In terms of the silver concentration, studies have reported that inhibitory doses higher than 10 µg mL −1 of different biogenic AgNPs inhibit P. syringae, either alone or combined with other antibiotics [35][36][37][38]. Thus, by using MnFe 2 O 4 /Ag-NC, we reported a further reduced concentration of silver acting efficiently against P. syringae when combined with essential oils.…”
Section: Antimicrobial Activity Of Mnfe 2 O 4 /Ag-nc Combined With Es...mentioning
confidence: 98%
“…Using the Scherrer formula, the crystalline size of NPs was calculated (C.s). Table 1 summarises the XRD data for experimental Ag NPs, including peak position, crystalline size variatio n, FWHM, interplanar spacing (dhkl), and miller index (hkl) [33,34].…”
Section: Structural Propertiesmentioning
confidence: 99%
“…The present cancer therapy challenges can be addressed through nanotechnology and nanoformulations 6 , 7 . Nanomaterials have shown peculiar natures and characteristics such as optical, magnetic, chemical, and mechanical properties, that allow multifaceted applications in food, healthcare, and agriculture 8 , 9 . Metal-based particles like gold (AuNPs) and silver (AgNPs) have drawn considerable interest in infectious diseases and post-surgical infections due to inherent bioactivities and lower possibility of toxicity to normal cells 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%